2013
DOI: 10.1080/09585192.2012.669783
|View full text |Cite
|
Sign up to set email alerts
|

Greeningthe airline pilot: HRM and the green performance of airlines in the UK

Abstract: This paper investigates the potential for human resource management (HRM) to influence the green performance of airlines. The focus is on the management of airline pilots, in particular, who have unparalleled opportunities to affect green performance through their control of the machines that directly impact the industry's carbon footprint. As a result it is vital that the HR function finds ways to engage them in the greening of the organization and works to reduce the triggers to actions that have the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 38 publications
7
100
0
3
Order By: Relevance
“…In particular, both researchers and practitioners have focused most of their attention on green training (such as awareness campaigns, training and induction) and involvement (such as bi-directional communication flows) (Daily and Huang, 2001;Harvey, Williams, & Probert, 2013;Daily, Bishop, & Massoud, 2012;Jabbour, 2013). Green training is also shown to be the most adopted practice among green HRM practices (CIPD, 2013).…”
Section: Hp2a Green Hiring Is Positively Related To Environmental Pementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, both researchers and practitioners have focused most of their attention on green training (such as awareness campaigns, training and induction) and involvement (such as bi-directional communication flows) (Daily and Huang, 2001;Harvey, Williams, & Probert, 2013;Daily, Bishop, & Massoud, 2012;Jabbour, 2013). Green training is also shown to be the most adopted practice among green HRM practices (CIPD, 2013).…”
Section: Hp2a Green Hiring Is Positively Related To Environmental Pementioning
confidence: 99%
“…For example, the CIPD recently reported that 21% of the HR managers surveyed included sustainability objectives as part of employees' performance assessment (CIPD, 2013). Green performance management and compensation practices guide employees' to align their behaviors with the environmental objectives of the organization (Govindarajulu and Daily, 2004;Harvey et al, 2013). Including environmental objectives as part of employee performance management is an effective way to signal to employees the firm's commitment to sustainability (Renwick et al, 2013).…”
Section: Hp2b Green Training and Involvement Is Positively Related Tmentioning
confidence: 99%
“…This is important when considering the potential environmental impact, including energy consumption, waste and carbon footprint, as this industry is accused of producing extensive wastage and a high carbon footprint. Current research focuses on manufacturing industries and ISO 14001-certified companies (Jabbour et al, , 2015Teixeira et al, 2012) and aviation (Harvey et al, 2013). Therefore, this comparative qualitative empirical study seeks to address these identified gaps in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The setting out of strategic priorities and objectives develops the 'content', the shift then needs to be made from content to 'process' which identifies the ways in which alignment between the overarching strategy and Green HRM strategic priorities can be achieved (Jackson & Seo, 2010). In addition, where firms are committed to greening their operations and embedding these clearly in their mission statements and strategies, the organizationally committed employee would be more inclined to work in a congruent and environmentally sound manner (Harvey, Williams, & Probert, 2013). Therefore, the positioning and alignment of the environment and HR function is essential to achieving environmental performance that seeks to translate strategy into operational practice.…”
Section: Introductionmentioning
confidence: 99%
“…As environmental sustainability requires behavior change by employees [45] and all members of an organization at all levels are required to exhibit a positive behavioral change. Thus, green behaviour influenced on green human capital by address the environmental issues possessed by individuals, shared and communicated throughout the organization in terms of knowledge, skills and awareness [46].…”
Section: The Influence Of Green Human Resource Management On Green Inmentioning
confidence: 99%